‘The Lucky Country’: How the COVID-19 Pandemic Revitalised Australia’s Lethargic Art Market - Anita Archer; David M. Challis (Arts, 2022)
Since its publication in 1964, Australians have used the title of Donald Horne’s book, The Lucky Country, as a term of self-reflective endearment to express the social and economic benefits afforded to the population by the country’s wealth of geographical and environmental advantages. These same advantages, combined with strict border closures, have proven invaluable in protecting Australia from the ravages of the global COVID-19 pandemic, in comparison to many other countries. However, elements of Australia’s arts sector have not been so fortunate. The financial damage of pandemic-driven closures of exhibitions, art events, museums, and art businesses has been compounded by complex government stimulus packages that have excluded many contracted arts workers. Contrarily, a booming fine art auction market and commercial gallery sector driven by stay-at-home local collectors demonstrated remarkable resilience considering the extraordinary circumstances. Nonetheless, this resilience must be contextualised against a decade of underperformance in the Australian art market, fed by the negative impact of national taxation policies and a dearth of Federal government support for the visual arts sector. This paper examines the complex and contradictory landscape of the art market in Australia during the global pandemic, including the extension of pre-pandemic trends towards digitalisation and internationalisation. Drawing on qualitative and quantitative analysis, the paper concludes that Australia is indeed a ‘lucky country’, and that whilst lockdowns have driven stay-at-home collectors to kick-start the local art market, an overdue digital pivot also offers future opportunities in the aftermath of the pandemic for national and international growth.